Reduction of Hepatitis A Virus on FRhK‐4 Cells Treated with Korean Red Ginseng Extract and Ginsenosides. Issue 9 (9th August 2013) - Lee, Min Hwa; Lee, Bog‐Hieu; Lee, Sanghyun; Choi, Changsun
Abstract: Red ginseng has a variety of bioactive functions and is widely used as an oriental medicinal herb and food ingredient. The aim of this study was to investigate the antiviral effect of red ginseng extract and ginsenosides against hepatitis A virus (HAV). To examine the antiviral effect against HAV, 0 to 10 μg/mL of red ginseng and purified ginsenoside Rb1 and Rg1 were pre‐treated or co‐treated on FRhK‐4 cells. The HAV titer decreased significantly in all groups pretreated with red ginseng or purified ginsenosides. The reduction of HAV was significant in FRhK‐4 cells pre‐treated only with red ginseng. Our results showed that red ginseng and ginsenoside Rg1 and Rb1 could decrease HAV titers.